Enhancing the Antimicrobial Activity of Alamethicin F50/5 by Incorporating N‐terminal Hydrophobic Triazole Substituents. Issue 71 (23rd November 2017) - Das, Sanjit; Ben Haj Salah, Khoubaib; Wenger, Emmanuel; Martinez, Jean; Kotarba, Jules; Andreu, Vanessa; Ruiz, Nicolas; Savini, Filippo; Stella, Lorenzo; Didierjean, Claude; Legrand, Baptiste; Inguimbert, Nicolas
Abstract: A simple and efficient strategy is proposed to significantly improve the antibacterial activity of peptaibols and other antimicrobial peptides by N‐terminal capping with 1, 2, 3‐triazole bearing various hydrophobic substituents on C‐4. Such N‐terminal insertions on alamethicin F50/5 could enhance its antimicrobial activity on Gram‐positive bacteria without modification of its overall three‐dimensional structure. Although the native peptide and its analogues shared comparable helical contents, the crystal structure of one of the most active derivative showed a local slight distortion of the N‐terminal extremity, which was also observed in solution using NMR spectroscopy. Importantly, fluorescence studies showed that the N‐capped derivatives had increased affinity for liposomes, which may indicate they interacted more strongly with the bacterial membrane than alamethicin F50/5. Abstract : Change the N‐terminal tail : 4‐aromatic substituted 1, 2, 3‐triazoles can be used for replacing the N ‐acetyl capping of peptides. These moieties were easily synthesized and introduced by solid phase peptide synthesis on antimicrobial peptaibols increasing their biological activity up to eight times without modification of overall three‐dimensional structure.